Rebound of Ankle Valgus Deformity in Patients With Hereditary Multiple Exostosis. Issue 1 (January 2015) - Rupprecht, Martin; Spiro, Alexander S.; Schlickewei, Carsten; Breyer, Sandra; Ridderbusch, Karsten; Stücker, Ralf
Abstract : Background: Temporary screw epiphysiodesis of the distal tibia is employed to correct ankle valgus deformity in patients with a wide spectrum of underlying etiologies. For patients with hereditary multiple exostosis it is unclear whether a rebound phenomenon may play a role after screw removal (SR) and successful management of ankle valgus deformity. Methods: From January 2002 to July 2013, 10 boys and 2 girls with HME and an ankle valgus deformity were included in this study. To be included the following criteria had to be met: patients had to have undergone temporary medial malleolar screw epiphysiodesis, SR at the time of skeletal maturity or correction of the deformity, a follow-up (FU) at least 6 months after SR, and consistent radiographs obtained preoperatively at the time of SR as well at FU. The average age at the time of operation was 11.6±1.5 years (range, 9.6 to 14.7 y). The tibiotalar tilt (TT) was analyzed preoperatively, at SR and at FU. Results: The average preoperative TT was 13.2±4.9 degrees. Twenty-four months (±10) after epiphysiodesis all screws were removed. At SR, the TT was normalized to 0.8±4.8 degrees ( P <0.001), according to an average rate of correction of 0.63±0.28 degrees per month. Twenty-two months (±13) after SR, the TT increased up to 3.2±4.9 degrees ( P <0.05), a rebound (>5 degrees) occurred in 43%, managed by repeated epiphysiodesis. No deep infections or implant complications occurred. No permanent damage of the physis was observed in any case. Conclusions: Medial malleolar screw epiphysiodesis is a successful treatment for the correction of ankle valgus deformity in patients with HME. A rebound after SR in the growing child or adolescent occurs in almost 50% of patients with HME, which can easily be managed by repeated epiphysiodesis. Therefore, we do not recommend overcorrection into a slight varus deformity. Because of the varying correction and recurrence rates, close FUs are of paramount importance. Level of Evidence: Level IV.